Think laterally: horizontal gene transfer from symbiotic microbes may extend the phenotype of marine sessile hosts - Degnan, Sandie M. (Frontiers in Microbiology, 2014)
Since the origin of the animal kingdom, marine animals have lived in association with viruses, prokaryotes and unicellular eukaryotes, often as symbionts. This long and continuous interaction has provided ample opportunity not only for the evolution of intimate interactions such as sharing of metabolic pathways, but also for horizontal gene transfer (HGT) of non-metazoan genes into metazoan genomes. The number of demonstrated cases of inter-kingdom HGT is currently small, such that it is not yet widely appreciated as a significant player in animal evolution. Sessile marine invertebrates that vertically inherit bacterial symbionts, that have no dedicated germ line, or that bud or excise pluripotent somatic cells during their life history may be particularly receptive to HGT from their symbionts. Closer scrutiny of the growing number of genomes being accrued for these animals may thus reveal HGT as a regular source of novel variation that can function to extend the host phenotype metabolically, morphologically or even behaviourally. Taxonomic identification of symbionts will help to address the intriguing question of whether past HGT events may constrain contemporary symbioses.